2012
DOI: 10.3310/hta16400
|View full text |Cite
|
Sign up to set email alerts
|

The use of MElatonin in children with Neurodevelopmental Disorders and impaired Sleep: a randomised, double-blind, placebo-controlled, parallel study (MENDS).

Abstract: How to obtain copies of this and other HTA programme reports An electronic version of this title, in Adobe Acrobat format, is available for downloading free of charge for personal use from the HTA website (www.hta.ac.uk). A fully searchable DVD is also available (see below).Printed copies of HTA journal series issues cost £20 each (post and packing free in the UK) to both public and private sector purchasers from our despatch agents.Non-UK purchasers will have to pay a small fee for post and packing. For Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 26 publications
2
117
0
Order By: Relevance
“…A prolonged-release formulation of melatonin is licensed for short-term treatment for primary insomnia in people aged 55 years or over 19. Unlicensed preparations of immediate-release melatonin are often prescribed for children who have difficulty sleeping 16. Although melatonin is thought to have few unwanted effects, there are concerns about its relationship to epileptic seizures, and delays in sexual maturation (reported in animal studies; effects on the onset of puberty in children are uncertain) 14,18…”
Section: About Melatoninmentioning
confidence: 99%
See 1 more Smart Citation
“…A prolonged-release formulation of melatonin is licensed for short-term treatment for primary insomnia in people aged 55 years or over 19. Unlicensed preparations of immediate-release melatonin are often prescribed for children who have difficulty sleeping 16. Although melatonin is thought to have few unwanted effects, there are concerns about its relationship to epileptic seizures, and delays in sexual maturation (reported in animal studies; effects on the onset of puberty in children are uncertain) 14,18…”
Section: About Melatoninmentioning
confidence: 99%
“…Melatonin reduced SOL measured by sleep diaries (−38 minutes, 95% CI −55 to −20, p<0.001) and actigraphy (−45 minutes, 95% CI −69 to −22, p<0.001). Seven serious adverse events were reported, of which two (one in the placebo group and one in the melatonin group) were considered related to the study drug in a blinded assessment 16,28…”
Section: About Melatoninmentioning
confidence: 99%
“…In a study of 21 children with ASD who also had epilepsy, there was no increase in seizure activity 6. Seizure exacerbation was not seen in the children with an established diagnosis of epilepsy in the MENDS trial (11% of the trial population) 7. The most common dose used in studies of melatonin for sleep disorders in children appears to be 3 mg, with a range of 1–10 mg. National Institute for Health and Care Excellence advice on melatonin in children with attention deficit hyperactivity disorder and sleep onset insomnia is based on three randomised controlled trials.…”
Section: Answermentioning
confidence: 99%
“…The dose was escalated through 2 mg, 6 mg to 12 mg during the first 4 weeks at the end of which the child was maintained on that dose. One hundred and forty-six children aged 3–15 years were randomised 7. At week 12, of the remaining 65 patients in the melatonin group, 38.5% were taking 12 mg.…”
Section: Answermentioning
confidence: 99%
“…Few studies reported results on the use of melatonin in children with neurodevelopmental disabilities (ND) including CP patients, even if not exclusively [6][7][8][9][10][11][12][13]. In these studies melatonin has been administered 30-60 minutes before the child's usual bedtime with a dose ranging from 0.5 to 12 mg for a period >4 weeks, showing an effect in both reducing the time to sleep onset or sleep latency and increasing the total duration of continuous sleep throughout the night.…”
Section: Opinionmentioning
confidence: 99%